(Swiss) GraphoLearn: an app-based tool to support beginning readers - Hannah Mehringer; Gorka Fraga-González; Georgette Pleisch; Martina Röthlisberger; Franziska Aepli; Vera Keller; Iliana I. Karipidis; Silvia Brem (The Asia-Pacific Society for Computers in Education (APSCE), 2020)
Abstract We assessed the Swiss-German version of GraphoLearn, a computer game designed to support reading by training grapheme-phoneme correspondences. A group of 34 children at risk for dyslexia trained three times a week during 14 weeks, on top of their standard school instruction. The sample was divided into two groups of 18 and 16 children, who started training at either the middle or the end of first grade. We found beneficial training effects in pseudoword reading in both training groups and for rapid automatized naming skills in the group that trained earlier. Our results suggest that both the efficiency in phonological decoding and rapid access to verbal representations are susceptible to facilitation by GraphoLearn. These findings confirm the utility of the training software as a tool to support school instruction and reading-related abilities in beginning readers. We discuss ideas to improve the content and outcomes of future versions of the training software.